Production Process Analysis and Improvement of Corrugated Cardboard Industry - Pereira, Maria Teresa Ribeiro (2020)
This work was developed into a corrugated cardboard industrial company. In this sector are produced plans resulting from the union between corrugated cardboard produced and the sheets printed in the previous sector. The PDCA cycle was the main methodology used in this work. Firstly, the initial state of the production was analyzed by data collection in both existent lines and it was concluded that a great variability of the parameters was being used in the process for similar works. The main problems in the process were identified and it was concluded that warp and detached plans were the main reasons for concern. It was implemented a set of measures to reduce these incidences. Control charts were implemented to the starch glue and through the analysis of these charts and cause-effect diagrams several changes to the starch glue circuit and to its own recipe were implemented. The steam pressure of the boiler was reduced from 12 bar to 8 bar and a table with temperatures regarding each paper weight was implemented. The results obtained show that the percentage of waste in the sector was reduced from values ranging between 9 and 12% to values around 4%. Regarding starch glue consumption, it dropped from 11 g/m2 to 8 g/m2. The energy consumption, namely gas, showed a saving of 9%. Thus, this work represents an important contribute to the sector, allowing energy savings and quality and competitiveness improvements.